TATA KELOLA ADMINISTRASI DESA DI DESA AKESIBU KECAMATAN IBU TENGAH KABUPATEN HALMAHERA BARAT - DJABU, FREDIK; POSUMAH, JOHNNY HANNY; TAMPI, GUSTAAF BUDDY (Sam Ratulangi University, 2019)
Village administration must be managed optimally by the administrator in order to provide effective and efficient guidance to the community. The purpose of this study was to find village administration governance in the of akesibu middle ibu district west halmahera regency. This study uses descriptive qualitative research methods. Data collection techniques used were interviews, documentation and data collection with documents to see how the village administration governance in the of akesibu middle ibu district west halmahera regency. The researcher used five indicators, namely: transparancy, accountability, responsibility, indenpendence, equality and fairness. The results of this study indicate that in the implementation of governance in the village of aces not all village administrations have been implemented in accordance with applicable rules that refer to the PERMENDAGRI No. 47 of 2016. Lack of experience from some village goverment offiicials to manage village administration, clash between personal work and pubilc interests, lack of equality in providing services to the community. Thus It can be concluded that the village administration governance in the of akesibu middle ibu district west halmahera regency has not been effective and efficient.Keywords: Governance, Village, Administration.